Diagnóstico da doença do enxerto-contra-hospedeiro aguda do trato gastrointestinal em pacientes submetidos a transplante alogênico de células-tronco hemapoéticas: estudo descritivo das alterações clínicas e dos exames complementares - Leticia Rocha Borges (2011)
Acute graft-versus-host disease (GVHD) is one of the major causes of morbidity and mortality in patients undergoing allogeneic hematopoietic stem -cell transplantation (AHSCT), and has thus become the subject-matter of several studies on understanding and treating it. This study does a descriptive analysis of apoptotic index evaluation and intestinal permeability alterations in association with the clinical, endoscopic and histopathological data on 31 patients undergoing AHSCT at the Transplant Unit of HC-UFMG, with emphasis on acute intestinal graft-versus-host disease (GVHD) diagnosis. Patients were divided into two groups one of patients with a clinical GVHD diagnosis and one of those with no clinical GVHD diagnosis. Thirteen deaths (41.9%) occurred during the study period among the 31 cases studied, thereby reaffirming the severity of the alterations found in the patients. F ifteen patients subjected to 21 esophagogastroduodenoscopy procedures prior to D+90 post-transplant had visible endoscopic alterations and 19 biopsies revealed histological alterations to their stomach and duodenum. We find higher apoptotic indices, not reaching statistical significance, in patients who died of graft versus host disease (GVHD), in the more acute forms of GVHD and where clinical GVHD was present. The results of intestinal permeability evaluation carried out on only nine patients in the three proposed periods showed alterations, some of which were pronounced even during pre-transplant, and, therefore, the pre-conditioning phase. Accordingly, this ?? is part of the effort to improve the methods for diagnosing acute gastrointestinal GVHD, with a view to a more accurate and early diagnosis.